Exposures to the tobacco retail environment among adolescent boys in urban and rural environments. (4th March 2019) - Burgoon, Montgomry L.; Albani, Thomas; Keller-Hamilton, Brittney; Lu, Bo; Roberts, Megan E.; Craigmile, Peter F.; Browning, Christopher; Xi, Wenna; Ferketich, Amy K.
ABSTRACT: Background : The tobacco industry spends billions on retail marketing and such marketing is associated with tobacco use. Previous research has not examined actual and potential exposures that adolescents have on a daily basis. Objective : The objective of this study was to determine whether both self-reported and geographically estimated tobacco retailer exposures differ by participant or neighborhood characteristics among urban and rural adolescents. Methods : The data for this study were part of a cohort study of 1220 adolescent males residing in urban and rural (Appalachian) regions in Ohio. The baseline survey asked participants how often they visited stores that typically sell tobacco in the past week (self-reported exposures). The number of tobacco retailers between home and school was determined using ArcGIS software (potential exposures). Adjusted regression models were fit to determine the characteristics that were associated with self-reported or potential exposures to retailers. Results : Adolescents who were non-Hispanic black or other racial/ethnic minority, had used tobacco in the past, and lived in rural areas had higher self-reported exposures. Urban adolescents, non-Hispanic black or other racial/ethnic minority, and those living in neighborhoods with a higher percentage of poverty had more potential exposures to tobacco retailers in their path between home and school. Conclusions : Rural adolescents had more self-reported marketing exposures than urban adolescents. However, urban adolescents had more potential tobacco exposures between home and school. Thus, point of sale marketing limitations might be a more effective policy intervention in rural areas whereas limits on tobacco retailers might be more effective for urban areas.